Sea ice floes dissipate the energy of steep ocean waves. Issue 20 (25th October 2015) - Toffoli, A.; Bennetts, L. G.; Meylan, M. H.; Cavaliere, C.; Alberello, A.; Elsnab, J.; Monty, J. P.
Abstract: A laboratory experimental model of an incident ocean wave interacting with an ice floe is used to validate the canonical, solitary floe version of contemporary theoretical models of wave attenuation in the ice‐covered ocean. Amplitudes of waves transmitted by the floe are presented as functions of incident wave steepness for different incident wavelengths. The model is shown to predict the transmitted amplitudes accurately for low incident steepness but to overpredict the amplitudes by an increasing amount, as the incident wave becomes steeper. The proportion of incident wave energy dissipated by the floe in the experiments is shown to correlate with the agreement between the theoretical model and the experimental data, thus implying that wave‐floe interactions increasingly dissipate wave energy as the incident wave becomes steeper. Key Points: Wave scattering theory alone is not sufficient to predict attenuation of waves Wave energy is not conserved during wave‐ice interactions Turbulent bores at the floes front and rear edges induce dissipation